2013
DOI: 10.4028/www.scientific.net/amm.295-298.1284
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Flocculation Technology for Copper and Zinc Ions Removal from the Tin Smelting Wastewater

Abstract: Magnetic flocculation technology was investigated for the removal of copper and zinc ions from simulated tin smelting wastewater, and the effects of magnetic powder dosage, flocculant dosage, and pH on the removal of copper and zinc ions were estimated. The results show that the effluent quality is poor with magnetic powder, PAC and PAM separately dosed, but when magnetic powder is combined with PAC or PAM, the excellent effluent quality is obtained with the removal rate of the copper and zinc ions of more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Urine is the primary source of ammonia nitrogen in swine wastewater, and the organic matter comes from residual feces. In the MC process, SS in the wastewater used the magnetic species as the core to form flocs (alum flowers), and flocs were settled with the gravitational force [ 23 ]. On the other hand, as an inorganic polymer, PAC could hydrolyze and polymerize to form various aluminum hydroxyl compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine is the primary source of ammonia nitrogen in swine wastewater, and the organic matter comes from residual feces. In the MC process, SS in the wastewater used the magnetic species as the core to form flocs (alum flowers), and flocs were settled with the gravitational force [ 23 ]. On the other hand, as an inorganic polymer, PAC could hydrolyze and polymerize to form various aluminum hydroxyl compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic adsorption and aggregation make the magnetic coagulation process more effective than conventional coagulation, improving the structure and strength of the flocs, thereby increasing the efficiency of solid–liquid separation and achieving sludge reduction [ 19 ] and removing suspended particles and colloidal substances in wastewater, thus reducing the chemical agent consumption and improving the removal efficiency [ 21 ]. As a cost-effective pre-treatment process, magnetic coagulation is being paid more and more attention, and it has been widely applied in high-strength wastewater treatment with high removal efficiencies of COD and TP [ 19 , 22 ] due to its effective removal of SS, COD, phosphate, and TP, which could mitigate the organic loading rate and improve the treatment performance for subsequent biological wastewater treatment processes [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the best pH is 6.5 and 7.5 according to the results of the first set, thus it was decided to take the average value (7) to determine the best alum dose at this average value of pH. It was found that 120 mg/L of alum gives the highest removal efficiency (Fig.…”
Section: Second Set Resultsmentioning
confidence: 99%
“…Various improvements are introduced to the coagulationflocculation process, such as using natural or synthetic polymers as a flocculant aids to strengthen flocs, employing another technology of separation with the coagulation-flocculation process, like magnetic flocculation. Its principle is adding particles of a higher magnetic susceptibility into a conventional coagulationflocculation process to enhance the flocculation velocity and form flocs of high density to settle quickly [7]. It combines a traditional flocculation and a magnetic separation in one process exhibiting a quick, simple, energyefficient, and cost effective advantages [8].…”
Section: Introductionmentioning
confidence: 99%